Elevated Levels of Estradiol in Human Immunodeficiency Virus–Infected Pregnant Women on Protease Inhibitor–Based Regimens. (24th August 2017) - Balogun, Kayode A; Guzman Lenis, Monica S; Papp, Eszter; Loutfy, Mona; Yudin, Mark H; MacGillivray, Jay; Walmsley, Sharon L; Silverman, Michael; Serghides, Lena
Abstract : HIV-infected pregnant women on protease inhibitor (PI)–based combination antiretroviral therapy (cART) had elevated estradiol levels compared with HIV-uninfected women. Estradiol levels in the fetal compartment (cord blood) were inversely correlated with birth weight centile in the HIV-infected, PI-cART–exposed women. Abstract: Background: Human immunodeficiency virus (HIV)–infected pregnant women on protease inhibitor (PI)–based combination antiretroviral therapy (cART) have a greater risk for adverse birth outcomes, and an association with steroid hormone levels has been implicated. The objective of this study was to investigate the association between PI-cART and estradiol levels in pregnancy. Methods: Fifty-five HIV-infected and 49 HIV-uninfected Canadian pregnant women were followed prospectively throughout gestation. All HIV-infected women were on a PI-based cART regimen. Maternal plasma samples were collected at 12–18 weeks, 24–28 weeks, 34–38 weeks, at delivery, and from the cord. Birth outcomes were recorded. Levels of estradiol, dehydroepiandrosterone sulfate (DHEAS), sex hormone–binding globulin (SHBG), cortisol, and adrenocorticotropic hormone (ACTH) were quantified by enzyme-linked immunosorbent assay. Results: (median [interquartile range] for cord estradiol: 23.9 ng/mL [16.4–36.4] for HIV-infected exposed to PI-cART and 15.7 ng/mL [12.2–21.2] for HIV-negative; P = .0025). HIV-infected women had higher DHEAS levels in cord plasma that correlated with cord and maternal delivery estradiol levels. Cortisol and ACTH levels did not differ between groups. In the HIV-infected women, cord estradiol levels correlated negatively with birth weight centile ( r = –0.47, P = .0016). Conclusions: Our data suggest that PI-cART exposure in pregnancy is associated with elevated levels of estradiol, likely driven by higher fetal DHEAS production. Cord estradiol levels were inversely correlated with birth weight centile in infants born to PI-cART–exposed women, suggesting that fetal exposure to high estradiol levels may be contributing to cART-associated fetal growth restriction.